Ortografia no Ensino Fundamental II: múltiplos padrões e (re)escrita textual - Marcelo de Castro (2022)
The spelling domain is relevant knowledge for writing proficiency and, consequently, for the full exercise of citizenship by students (MORAIS, 2014). However, the obscuration in the study of smaller units of the language, such as the grapheme, is one of the explanations for the permanence of diversified spelling errors in formal student writing. Contrary to this and other prejudiced pedagogical concepts and practices around the orthographic norm, this research aimed to reflect on the learning and teaching of orthography from: i) the analysis of the most persistent orthographic errors in the textual (re)writing of students from the 7th grade of Elementary School and ii) the relationship between the type of correction (resolutive/indicative) used by the teacher-researcher between the first version of the text and the refactoring with regard to orthographic writing. Therefore, the investigation was based mainly on the Integration of Multiple Patterns (TREIMAN; KESSLER, 2014). Methodologically, the study was applied in nature and had a qualitative-quantitative approach (PAIVA, 2019). The corpus, generated from March to November 2019, was composed of 199 (re)written texts produced by 7th grade students, enrolled in a private school in Belo Horizonte (Minas Gerais). Through the identification, quantification and categorization of data, it was found that the exchange, deletion and addition of graphemes were, respectively, the categories with the highest percentage of spelling errors. In this triad, there were, in particular, inconsistent spellings regarding the orthographic representations for the phonemes /s/ and /i/, due, for example, to the complexity in the orthographic representation of the first and to the phonological processes (raising, monophthongization and diphthongization) that materialize in the writing of the second. The phonological pattern – Portuguese orthography basis – was the most used to elucidate the understanding around such errors, but other graphic and linguistic patterns were part of this discussion. In addition, it was confirmed that rewriting is an effective methodology for reducing incorrect spellings compared to the first version of the text. Through statistical tests, it was also demonstrated that there was no statistical significance between the resolutive and the indicative intervention regarding the production of correct spellings, the maintenance of orthographic errors and the elimination of these in the texts that were rewritten. Even so, it was argued that the indication is more pertinent to spelling correction, as it provides an opportunity for a dialogic process between teacher and student, having this active role in the formulation of new hypotheses and in the reflection on the language. The dynamics inherent to the learning of orthographic (re)writing was still systematized, permeated by cases of oscillation in the spelling of the same word; of longitudinal persistence of spelling error; of producing new unsuccessful and successful graphic hypotheses, etc. Therefore, it was reinforced that learners need to have moments to think about orthography as an object of investigation and that the learning (and, consequently, the teaching) of orthographic writing is a non-linear and unfinished process that cannot be neglected by the school. In addition, it is concluded that spelling errors should be seen as clues to what needs to be explored didactically, a fact that demands an investigative attitude from the teacher on the spelling itself, as well as on the development of this linguistic facet.